Retooling For Terminated Contract Workers Of Vocational School Alumni (Back) To Work - Samidjo Samidjo (Universitas Sarjanawiyata Tamansiswa, 2019)
Abstract. Unemployment of vocational high school graduates consists of two categories, the graduates who never been in work and who had been in work as a contract workers and then terminated. More than 63 percent of the graduates who have ever been as a contract workers did not work match with their competence, as a result when the contract agreement expired the workers did not been assigned as permanent workers. In order to get other jobs after termination,Â the workers need to upgrade their competence or to retool with skills other than the skills the workers acquired from vocational school, in order to fit well with the need of workers in industry. Besides the functional skill needed for handling operational works, the terminated contract workers need to upgrade their soft skill suitable for the future working environment, that is learning to work in a group consisting of many communities to solve very complex problem as the characteristic of jobs in the industry 4.0, besides other component of soft skills such as honesty, discipline, attitude, commitment to work, communication skill, and open for change.